Broad spectrum photon responsive, paramagnetic beta-NaGdF4: Yb3+, Er3+ - mesoporous anatase titania nanocomposite - Padhye, Preeti; Sadhu, Subha; Malik, Monika; Poddar, Pankaj (RSC Advances, 2016)
Herein, we report a novel single multifunctional platform based on broad-spectrum photoactive beta-NaGdF4:18% Yb3+, 2% Er3+ and mesoporous anatase TiO2 for enhanced energy and simultaneous biomedical applications. Currently, the photoactive materials for solar energy harvesting applications have limitations in their efficiency due to their narrow photon absorption spectrum. The upconversion phosphor beta-NaGdF4: 18% Yb3+, 2% Er3+ nanorods collect and harvest the NIR photons (similar to 980 nm) of sunlight and transform them into visible light via anti-Stokes emission (lambda(em) similar to 521 and similar to 540 nm), and the photoactive mesoporous anatase TiO2 (mTiO(2)) utilizes UV and weak visible photons, thus the composite forms a broad spectrum photon-capture system and improved power conversion efficiency for enhanced applications in photocatalysis, and dye sensitized solar cells (DSSCs). The photocatalytic activity of the nanocomposite showed an improvement in comparison to the mTiO(2) for the degradation of various dyes. In addition, the photocurrent density and solar cell efficiency of the nanocomposites showed an improvement by similar to 24% and similar to 17% respectively, over mTiO(2). The beta-NaGdF4: Yb3+, Er3+/mTiO(2) nanocomposite exhibits a strong paramagnetic signal (chi similar to 6.45 x 10(-5) emu g(-1) Oe(-1)). The nuclear magnetic resonance (NMR) measurements showed large longitudinal T1 relaxivity (r(1) = 7.09 s(-1) mM(-1)) and magnetic resonance imaging showed enhanced T-1-weighted MRI images with increased concentrations of beta-NaGdF4: Yb3+, Er3+/mTiO(2) nanocomposite making them suitable for simultaneous magnetoresonance imaging. In addition, this composite system can also be used as a NIR triggered drug delivery system and in biomedical applications. Moreover, mesoporous TiO2 is expected to increase the photocatalytic active sites, dye, and absorption, and drug loading capacity. The as-designed multifunctional beta-NaGdF4:Yb3+, Er3+/mTiO(2) nanocomposite possessed simultaneous multiple discrete functionalities with excellent luminescence properties, intrinsic paramagnetism, biocompatibility, improved photocatalytic activity, and solar cell efficiency. This work provides a promising system to utilize NIR light, which will contribute to efficient photon harvesting and biological applications.

Downconversion luminescence-based nanosensor for label-free detection of explosives - Malik, Monika; Padhye, Preeti; Poddar, Pankaj (Acs Omega, 2019)
We report a selective and sensitive nanosensor probe based on polyethylenimine (PEI)-capped downconverting nanophosphors beta-NaYF4:Gd3+, Tb3+@PEI for the detection of 2,4,6-trinitrotoluene (TNT), both in water and buffer media. These downconverting phosphors were synthesized via a hydrothermal route and are known to show excellent chemical, thermal, and photostability. They emit sharp emission peaks centered at similar to 488, 544, 584, and 619 nm, among which the peak at similar to 544 nm was remarkably quenched (similar to 90%) by the addition of TNT without giving any new emission peak. The sensing mechanism is based on the formation of a Meisenheimer complex between the electron-rich amine-functionalized beta-NaYF4:Gd3+, Tb3+ nanophosphors and electron-deficient TNT molecule, which was prominently visualized by the change in the color of the solution from whitish to brownish yellow, enabling visual detection, followed by luminescence resonance energy transfer between the nanophosphors and the complex. A linear range for TNT detection was obtained from 0.1 to 300 mu M with a limit of detection as low as 119.9 nM. This method displayed excellent selectivity toward TNT over other nitroaromatic compounds, which had no influence on the detection. Moreover, various other classes of analytes, viz., amino acids, pesticides, and sugars, did not quench the luminescence intensity of the nanophosphors. This developed nanosensor probe possesses high, stable fluorescence brightness and capability for the selective and sensitive on-site recognition of TNT molecules in aqueous media, avoiding complicated strategies and instruments. Thus, this work promises to pave ways to many applications in the detection of ultratrace analytes.

Study of interfacial adhesion between nickel-titanium shape memory alloy and a polymer matrix by laser surface pattern - Samal, Sneha; Tyc, Ondrej; Heller, Ludek; Sittner, Petr; Malik, Monika; Poddar, Pankaj; Catauro, Michelina; Blanco, Ignazio (Applied Sciences-Basel, 2020)
The aim of this article is to investigate the interfacial adhesion of Ni-Ti shape memory alloy with a polymer matrix of Poly (methyl methacrylate) (PMMA). The surface pattern on Ni-Ti plates was channeled by a solid state laser machine. The laser machine allows for creating channels on the Ni-Ti surface for infiltration of the PMMA matrix, which could be attached as an intra-surface locking pattern to the Ni-Ti surface. The influence of the PMMA matrix on the surface of the NiTi plate was evaluated by thermomechanical analysis (TMA) and dynamic mechanical analysis (DMA). The surface characterization was carried out by an optical microscope on the PMMA/NiTi composite after mechanical testing. During mechanical testing, the polymer displays the multiple cracks in the longitudinal direction that result in slipping and fracture. TMA and DMA analyses were performed on the Ni-Ti- and PMMA-coated Ni-Ti ribbon to observe elasticity and the storage modulus for both samples. Better adhesion than 80 % was observed in the Ni-Ti surface, in the laser surface pattern, in comparison to the free plain surface. However, the polymer acts as mechanical backing that caused a reduction in the shape-memory properties of the composite material.
Keywords: adhesion; mechanical properties; NiTi composites; NiTi plate; PMMA; Polymer; surface features

Raman spectroscopy-based sensitive, fast and reversible vapour phase detection of explosives adsorbed on metal-organic frameworks UiO-67 - Sen Bishwas, Mousumi; Malik, Monika; Poddar, Pankaj (New Journal of Chemistry, 2021)
In this work, we report highly sensitive, selective, rapid, and reversible detection of explosive molecules in the vapour phase, adsorbed on metal-organic frameworks (MOFs) under ambient laboratory conditions. The sensing is based on the quenching of the Raman intensity of a zirconium-based MOF, Zr6O4(OH)(4)(dcppy)(6) (MOF 1, UiO-67-dcppy; dcppy is 2-phenylpyridine-5,4'-dicarboxylate), where 50% of the signal quenches swiftly within similar to 5 s of its exposure to trinitrophenol (TNP) vapours, while 90% of the Raman signal was quenched in 30 s. The high surface area of porous MOFs provides increased adsorption of various nitro analytes. The quenching of Raman peaks resulted from the pi-pi interactions of the analytes with the benzene ring of the MOF. The sensors have also been proven to be reversible and stable by mild heat treatment (80 degrees C for 5 min). These notable results using Raman spectroscopy point to a new and important approach towards explosive sensing using metal-organic frameworks considering their vast versatility. This work emphasizes the importance of a non-invasive and non-destructive technique that can be used to develop handheld vapour phase explosive detectors.